CSC567: Temporal Media Processing / College of Computing, Informatics and Media - UiTM, College of Computing, Informatics and Media (Universiti Teknologi MARA (UiTM), 2022)
This course provides a broad introduction to multimedia signal processing. The course is designed to provide students with the fundamentals of discrete-time signals, signal transforms, and digital filter design. Through this course, students are expected to achieve a basic understanding of digital signal processing and various compression methods.